Menstrual cycle and sporting performance perceptions of elite volleyball players - Ergin, E.; Kartal, A. (International Journal of Applied Exercise Physiology, 2020)
The present study aimed to investigate menstrual cycle and sporting performance perceptions of elite volleyball players. The study was participated by 130 volunteering volleyball players who play in the Turkish Volleyball Sultans` League and the 1st League [...] consisting of 25 questions about general and sporting performance before, during and after the menstrual cycle which was developed by the researcher upon receiving expert opinion. According to the study results; 61,5% of the participants described their general menstruation states as regular and 84,6% of them stated that they had menstrual problems due to sports. In addition, 58,5% of the volleyball players feel bad before menstruation while 52,3% feel themselves good during menstruation. Moreover, the responses show that menstrual periods of 46,2% of the participants sometimes affect their sports/training participation and 99,2% participate in competitions during this period. The volleyball players listed the problems they have during their menstrual periods as irritability (36,2 %) and anger (47,7%.); and 45,4% think that menstruation sometimes affects their sporting performance whereas 35,4% consider it does not. In conclusion, it can be said that female volleyball players do not experience such menstrual problems as delayed menarche, amenorrhea and oligomenorrhea and sports does not change menstrual period and that menstruation affects sporting activity rather psychologically.